Hubungan Tingkat Pengetahuan 3M terhadap Perilaku 3M Terkait COVID-19 pada Satpam Bank di Kabupaten Sintang Kalimantan Barat - Lusiana Safitri; Dewi Indah Lestari (Syntax Idea)
The importance of knowledge of the 3M health protocols on 3M behavior in breaking the chain of infectious disease transmission, especially Covid-19. Health protocols that should be followed by all layers of society during activities are known as the 3M (washing hands, wearing masks, and maintaining distance). This research aims to determine the relationship between the level of knowledge of the 3M health protocols and 3M behavior among bank security guards in Sintang Regency, West Kalimantan. The research methodology used is analytical with a cross-sectional design. The study population consists of bank security guards in Sintang Regency who are actively on duty and willing to fill out a questionnaire from December 2021 to May 2022. Univariate data will be presented in tabular form (characteristics, frequencies, and percentages). Bivariate data will be displayed in tables and analyzed using cross-tabulation and the chi-square test. In the chi-square test, a significance value (p-value) of < 0.05 is obtained, indicating a relationship between the knowledge level of the 3M health protocols and 3M behavior related to COVID-19 among bank security guards in Sintang Regency, West Kalimantan.